HbNIN2, a cytosolic alkaline/neutral‐invertase, is responsible for sucrose catabolism in rubber‐producing laticifers of Hevea brasiliensis (para rubber tree). Issue 2 (8th January 2015) - Liu, Shujin; Lan, Jixian; Zhou, Binhui; Qin, Yunxia; Zhou, Yihua; Xiao, Xiaohu; Yang, Jianghua; Gou, Jiqing; Qi, Jiyan; Huang, Yacheng; Tang, Chaorong
Summary: In Hevea brasiliensis, an alkaline/neutral invertase (A/N‐Inv) is responsible for sucrose catabolism in latex (essentially the cytoplasm of rubber‐producing laticifers, the source of natural rubber) and implicated in rubber yield. However, neither the gene encoding this enzyme nor its molecular and biochemical properties have been well documented. Three Hevea A/N‐Inv genes, namely HbNIN1, 2 and 3, were first cloned and characterized in planta and in Escherichia coli . Cellular localizations of HbNIN2 mRNA and protein were probed. From latex, active A/N‐Inv proteins were purified, identified, and explored for enzymatic properties. HbNIN2 was identified as the major A/N‐Inv gene functioning in latex based on its functionality in E. coli, its latex‐predominant expression, the conspicuous localization of its mRNA and protein in the laticifers, and its expressional correlation with rubber yield. An active A/N‐Inv protein was partially purified from latex, and determined as HbNIN2. The enhancement of HbNIN2 enzymatic activity by pyridoxal is peculiar to A/N‐Invs in other plants. We conclude that HbNIN2, a cytosolic A/N‐Inv, is responsible for sucrose catabolism in rubber laticifers. The results contribute to the studies of sucrose catabolism in plants as a whole and natural rubber synthesis in particular.